PepOSX-AI: CPP - an interpretable transformer-based deep learning model for prediction of cell-penetrating peptides - Haowen Chen; Weiwei He; Kaiyan Feng; Rong Xu; Sheng Yin; Lin Zheng; Jing Chen; Mouming Zhao; Jucai Xu; Lijun You (Analytica Chimica Acta, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Chitosan oligosaccharides activate PPARγ to alleviate aflatoxin B1-induced testicular inflammation and barrier damage - Pei-Yu Dong; Zhuang-Bing Li; Sheng-Lin Liang; Xi-Feng Zhang; Yan-Ni Feng; Wei You (Food Bioscience, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Antioxidant capability of peanut shell extracts obtained using an ethanol–ammonium sulfate two-phase system - Yung-Sheng Lin; Cheng-Kun He; Yun-En Jian; Ming-Ren Chen; Tz-Feng Lin; Cheng-You Chen; Wei-Hsun Wang (Biomass and Bioenergy, 2026)

Molecular dynamics simulation on microscopic water evaporation process from montmorillonite surface - Yue You; Chao-Sheng Tang; Siqi Zhang; Zhu-Yuan Lin; Tao Wang (Computers and Geotechnics, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Simultaneous remediation of polycyclic aromatic hydrocarbons (PAHs) contaminated soil using integrated steam-assisted plasma - Kevin Daffa Prasetya; Dwi Rasy Mujiyanti; Jhong-Lin Wu; Sheng-Jie You; Ya-Fen Wang (Environmental Research, 2025)

A new 2-arylbenzofuran derivative and other constituents from Smilax china L. and their chemotaxonomic significance - Li-Juan Hu; Xian-Sheng Ye; Kuan Lin; Jie Gao; De-Sen Yang; Guo-Ping Gan; Xi-Ji Shu; Wei Liu; You-Hua Yang (Biochemical Systematics and Ecology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Assessing current distribution and climate-driven potential invasion areas of Lycorma delicatula, with a focus on Taiwan - You-Sheng Lin; Jhih-Rong Liao (Biological Invasions, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Discovering potential fumigants against Tribolium castaneum from essential oils using GC-MS and chemometric approaches - Yan Yan Lin; Min Xing Zhang; Miao Sun; Lu Sheng Wan; You Zhou; Jing Sheng Chen (Journal of Stored Products Research, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Quantify the effects of water-soluble salts and available fractions of nutrient elements on mobility of cadmium in paddy soil: A case study of the Pearl River Delta - Changchen Huang; Weikang Sheng; Qingye Hou; Zhongfang Yang; Tao Yu; Yuanhang You; Kun Lin; Cheng Li (Journal of Cleaner Production, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Lead-rivet strategy of growing perovskite nanocrystals for excellent toxicity inhibition and spinning application - Hanlong Wang; Shifeng Zhu; Jiaoyue Sheng; Feihong Gao; Lei Yang; Xili Hu; Francisco Fernández-Martínez; Longhui Lin; Chaoyu You; Dongming Xing (Journal of Hazardous Materials, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Perspective on intestinal microbiota temporal changes of herbal additives treated shrimp in a natural aquaculture setting - Xu-Yin Lin; Yi-Jia Shih; Xian-Jing Zhang; You-Shu Cai; Xiao-Wen Zhou; Jung-Sheng Chen (Frontiers in Marine Science, 2024)
Shrimp is an important aquaculture species worldwide. The use of antibiotics to suppress disease outbreaks has led to antibiotic resistance; however, probiotics or natural herbal additives can enhance the health of farmed shrimp. In this study, the effects of formulations containing natural herbs and probiotics on shrimp farming were explored. Following indoor shrimp farming, the shrimp were returned to outdoor natural ponds for 1 week in the presence of a fermented probiotic product. The gut microbiota was surveyed using 16S rRNA gene sequencing at 1, 2, 3, and 8 weeks after the natural pond release. The results showed that Vibrio -related bacterial genera increased significantly in the shrimp intestinal microbiota at 2 weeks and were particularly high at 3 weeks after natural pond release. The phyla Firmicutes, Bacteroidetes, Vibrio -related bacteria, and the genus Cetobacterium emerged as crucial bacteria linked to shrimp health and growth. Overall, the diversity of the shrimp intestinal microbiota was lower upon release into the natural pond. However, this outcome may be associated with dysbiosis or influenced by the natural environment. Further research is warranted to substantiate these findings. A perspective on the shrimp gut microbiota provides important information for aquaculture management and explains the implementation of control measures.

Aflatoxin B1 affects porcine alveolar macrophage growth through the calcium signaling pathway mediated by the ceRNA regulatory network - Yu Tian; Pei-Yu Dong; Sheng-Lin Liang; Long Li; Shu-Er Zhang; Francesca Gioia Klinger; Wei Shen; You-Yu Yan; Xi-Feng Zhang (Molecular Biology Reports, 2023)

Direct synthesis of CH3OH from CO2 hydrogenation over Ni5Ga3/SiO2 catalysts - Kuen-Song Lin; Abrar Hussain; You-Sheng Lin; Yung-Chen Hsieh; Chao-Lung Chiang (Fuel, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

Potential risk of eutrophication in the deepest lake of Southwest China: Insights from phosphorus enrichment in bottom water - You-ai Duan; Xin-sheng Chen; Ying Huang; Yan Zhang; Ping Wang; Xue-xin Duan; Xian-yan Qin; Ye-ai Zou; Zheng-miao Deng; Qi-lin Zhao (Journal of Contaminant Hydrology, 2023)

Screening of structural and functional alterations in duckweed (Lemna minor) induced by per- and polyfluoroalkyl substances (PFASs) with FTIR spectroscopy - Ying-Lin Wu; Qian Xiong; Ben Wang; You-Sheng Liu; Pei-Liang Zhou; Li-Xin Hu; Fang Liu; Guang-Guo Ying (Environmental Pollution, 2023)

The emergence of prolonged deadly humid heatwaves - Xiang‐Sheng Wang; Lei He; Xiao‐Hu Ma; Qiang Bie; Lin Luo; You‐Cai Xiong; Jian‐Sheng Ye (International Journal of Climatology, 2022)
Deadly humid heat conditions exceeding human thermoregulatory capacity have been reported; however, whether and where the deadly humid heat events occur consecutively across the land surface are largely unknown. We calculate the maximum consecutive days of deadly humid heat, defined as daily maximum wet‐bulb temperature (TWmax) ≥35°C, for observations of 9,278 meteorological stations and for simulations of 14 global climate models. We further define short and long deadly humid heatwaves as a period of 3–4 and ≥5 consecutive days with daily TWmax ≥35°C, respectively. Our analyses show that six stations in some subtropical regions have experienced deadly humid heat with daily TWmax ≥35°C, but only occurs in individual days. Deadly humid heatwaves increase exponentially as the global mean temperature rising. When limiting global warming within 1.5°C, long deadly humid heatwaves will not occur across the land surface, and short deadly humid heatwaves will only emerge in some drylands but not in humid areas. Under 2°C warming, 0.09% of the global land, 0.42% of the human population, and 0.56% of the global centres of crop diversity are projected to be exposed to long deadly humid heatwaves. Meanwhile, 18% of the deadly humid heatwaves lasting ≥3 consecutive days will occur in humid areas; the fractions are projected to rapidly increase in humid areas as temperature rising further. At the end of the century, the percentage of land areas and human population exposed to deadly humid heatwaves lasting ≥3 consecutive days are expected to be 76‐times higher than that under 1.5°C warming level. Our finding suggests that keeping global warming within 1.5°C will significantly constrain the emergence of prolonged deadly humid heatwaves and thus reduce the risk of the human population especially outdoor agricultural workers.

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Numerical Investigation of the Characteristics of Erosion in a Centrifugal Pump for Transporting Dilute Particle-Laden Flows - Rui-Jie Zhao; You-Long Zhao; De-Sheng Zhang; Yan Li; Lin-Lin Geng (Journal of Marine Science and Engineering, 2021)
Erosion in centrifugal pumps for transporting flows with dilute particles is a main pump failure problem in many engineering processes. A numerical model combining the computational fluid dynamics (CFD) and Discrete Element Method (DEM) is applied to simulate erosion in a centrifugal pump. Different models of the liquid-solid inter-phase forces are implemented, and the particle-turbulence interaction is also defined. The inertial particles considered in this work are monodisperse and have finite size. The numerical results are validated by comparing the results with a series of experimental data. Then, the effects of particle volume fraction, size, and shape on the pump erosion are estimated in the simulations. The results demonstrate that severe erosive areas are located near the inlet and outlet of the pressure side of the impeller blade, the middle region of the blade, the corners of the shroud and hub of the impeller adjoining to the pressure side of the blade, and the volute near the pump tongue. Among these locations, the maximum erosion occurs near the inlet of the pressure side of the blade. Erosion mitigation occurs under the situation where more particles accumulate in the near-wall region of the eroded surface, forming a buffering layer. The relationship between the particle size and the erosion is nonlinear, and the 1 mm particle causes the maximum pump erosion. The sharp particles cause more severe erosion in the pump because both the frequency of particle-wall collisions and the impact angle increase with the increasing sharpness of the particle.

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Biological Protective Effects Against Vibrio Infections in Grouper Larvae Using the Strombidium sp. NTOU1, a Marine Ciliate Amenable for Scaled-Up Culture and With an Excellent Bacteriovorous Ability - Hung-Yun Lin; Wei-Yu Yeh; Sheng-Fang Tsai; Kuo-Ping Chiang; John Han-You Lin; Che-Chia Tsao; Han-Jia Lin (Frontiers in Marine Science, 2020)

Impacts of elevated temperature and pCO2 on the brooded larvae of Pocillopora damicornis from Luhuitou Reef, China: evidence for local acclimatization - Lei Jiang; Ming-Lan Guo; Fang Zhang; Yu-Yang Zhang; Guo-Wei Zhou; Xin-Ming Lei; Xiang-Cheng Yuan; You-Fang Sun; Tao Yuan; Lin Cai; Jian-Sheng Lian; Sheng Liu; et al. (Coral Reefs, 2020)

Analysis of endophytic bacterial community diversity and metabolic correlation in Cinnamomum camphora - Guo-fang Zhang; Qiu-liang Huang; Xue-qin Bi; You-lin Liu; Zong-sheng Yuan (Archives of Microbiology, 2020)

New pyridocarbazole alkaloids from Strychnos nitida - Wei Li; Gui-Hua Tang; Lin Chen; Ya-Qi Tang; You-Kai Xu; Bo Liu; Sheng Yin (Natural Product Research, 2018)

Transcription profiling and identification of infection-related genes in Phytophthora cactorum - Xiao-Ren Chen; Shen-Xin Huang; Ye Zhang; Gui-Lin Sheng; Bo-Yue Zhang; Qi-Yuan Li; Feng Zhu; Jing-You Xu (Molecular Genetics and Genomics, 2018)

MiR-26a functions as a tumor suppressor in ambient particulate matter-bound metal-triggered lung cancer cell metastasis by targeting LIN28B–IL6–STAT3 axis - Yan-Yang Lu; Yi Lin; Dong-Xiao Ding; Shu Su; Qiao-Qiao Chi; You-Chi Zhang; Jian Sun; Xu Zhang; Hui-Min Zhu; Qian-Sheng Huang; Yu-Lang Chi; Guo-Zhu Ye; et al. (Archives of Toxicology, 2018)

Multi-type sensor placement and response reconstruction for building structures: Experimental investigations - Rong-Pan Hu; You-Lin Xu; Sheng Zhan (Earthquake Engineering and Engineering Vibration, 2018)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

Landslides and catchment sedimentation in the Ta-Chia River influenced by the 1999 Taiwan Chi-Chi earthquake - Keh-Jian Shou; Li-Yuan Fei; Jiin-Fa Lee; Cheng-Yueh Wei; Sheng-Tsi Huang; You-Chang Lin (International Journal of Remote Sensing, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

The glycosides from Lomatogonium rotatum - Yu-Lin Li; You-Rui Suo; Zhi-Xin Liao; Li-Sheng Ding (Natural Product Research, 2008)

Stereoselective glucuronidation of carvedilol by Chinese liver microsomes - Lin-ya You; Chun-na Yu; Sheng-gu Xie; Shu-qing Chen; Su Zeng (Journal of Zhejiang University-SCIENCE B, 2007)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)